Development of Happiness in the Contemporary World: : From GDP to Doughnut Economics - Günay, Eylül Kabakçı; Kışla, Gül Huyugüzel; Türkcan, Burcu; Yenilmez, Meltem İnce (Social Sciences E-Books Online, Collection 2025, 2025)
Development of Happiness in the Contemporary World challenges how we measure success, asking: Is GDP enough to define progress?. This book takes you on a journey from traditional economic measures to groundbreaking models like Doughnut Economics, blending cutting-edge research with compelling examples. It uncovers how alternative frameworks better capture well-being, sustainability, and equity in today's world. Featuring rare insights and fresh data, it connects economic theory with real-life solutions to global challenges. Whether you're a policymaker, economist, or curious reader, this book equips you with the tools to rethink prosperity and create a happier, more sustainable future. Contributors are: Nermin Akarçay, Merve Özcan Altan, Barış Çağirkan, Arif Bağbaşlioğlu, Necmettin Çelik, Gözde Ersöz, Eylül Kabakçi Günay, Gökmen Kantar, Gül Huyugüzel Kişla, Özge Kozal, Begüm Yurteri Kösedağli, Burcu Türkcan, Ulviye Tüfekçi Yaman, Meltem İnce Yenilmez, and Hakan Yildirim.